The adoption of social learning systems in higher education: Extended TAM - Syarilla Iryani, A.S.; Bamansoor, S.; Kayode, B.; Alhazmi, A.K. (2018)
This study adopts the Technology Acceptance model (TAM) to identify the successful factors that influence student's intention to use social network learning system. The TAM proposed by Davis was the theoretical basis of the research. The researcher then extended TAM incorporating (self-efficacy, facilitating conditions, technology awareness, computer and internet training, social norm and information quality) to identify the successful factors effecting the student's intention to use social network learning system. Results of this study found that Information Quality (IQ) is the most influential factor on student's intention to use social learning system, followed by Perceived Usefulness (PU), and Facilitating Condition (FC) respectively.